Sutures génériques et fêlures intérieures chez Charles Burns - Jean-Paul Gabilliet (Sillages Critiques)
Charles Burns’ comics typify an aesthetics of the in-between unfolding on several levels. His pictorial narratives are suffused by colliding influences that convey a sense of unsettling strangeness close to Freudian Unheimlichkeit. He stitches together genres, motifs, and styles at a literally sub-liminal level with a dual creative agenda. First he achieves the miscegenation of two major visual styles of comic art, US 1950s-style noir brush inking and Franco-Belgian Hergé-style clear line. Second he causes genres to clash together by blending narrative clichés from the Fifties’ and Sixties’ most lowbrow pulp fiction and B-movies into quasi-surrealistic plots. Genre stitching results in the hybridization of characters and narratives. Yet whereas the seams between schlocky narrative formulas have become invisible the reader is repeatedly invited to become aware of them by means of various devices of permeability, such as fissures, cracks, orifices but also disease-infected skins and encounters between fictional worlds.